Internationalization of Paraguayan companies. An analysis of its development during 2002-2012 - Cabral López, María Antonella (2017)
This research focuses on the international development of Paraguayan companies in the period 2002-2012. The aim is to characterize these companies and their process of expansion. Thus, bibliographic and documentary evidence will be used in addition to field research, with a qualitative approach at a descriptive level. Among the main findings, it can be seen that international Paraguayan companies are large companies with a lot of experience in the local market; they are mainly engaged in the production of goods with low level of industrialization; they have sought to internationalize and expand their markets, generate greater revenue and increase their size.